Perancangan Video Motion Graphics Sosialisasi Stunting Bagi Remaja Usia 15-19 Tahun Di Kabupaten Manokwari - Ester Setiabudi; Michael Bezaleel Wenas; Penina Inten Maharani; Jasson Prestilano (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The high stunting rate in Manokwari makes Manokwari Regency the district with the highest stunting rate in West Papua Province. One of the factors causing the high stunting is the high rate of early marriage. This is due to the difficulty of understanding stunting. The government has made various efforts to reduce stunting but people still feel that they do not understand the material presented in socialization activities, moreover the material cannot be accessed repeatedly, especially for adolescents aged 15-19 years. Video motion graphics can be a solution to convey stunting information to the public. The research aims to design videos of less than one minute that contain illustration, animation, text and backsound, so that information can be conveyed in a more interesting way. The research method used is descriptive qualitative the result of this research is that motion graphics videos can be a medium for delivering socialization about stunting, especially early marriage, which can increase the information of the target audience who watch the video, especially for adolescents aged 15-19 years in Manokwari Regency. Keyboards : Stunting, Early Age Marriage, Motion graphics